Isolation and Identification of Mold Contaminants on Mushroom Growing Medium (Bag Log) and Their Cellulolytic Performance Test - Handayani, Tatik; Purwantisari, Susiana (JURNAL SAINS DAN MATEMATIKA, 2015)
Mushrooms naturally grows on logs that have experienced weathering. Raw materials of mushroom growth media containing plenty of wild microbes, especially wild mold on sawdust media. Sterilization conducted did not prevent the occurrence of contamination. This study aim was to determine the types of contaminant molds in cultivated mushroom growth media (bag logs), as well as determine their cellulolytic performance. Mushroom growth media (bag log) samples were taken from three mushroom cultivation locations. Mold isolates obtained were identified by their macroscopic and microscopic characteristics. Test the mold cellulolytic performance was conducted by measuring the ratio of hydrolysis zone with the diameter of mold on CMC (Carboxy Methyl Cellullose) media. The isolation and identification results of contaminant molds consisted of mold isolates which could be grouped into 7 genus which were Aspergillus, Penicillium, Paecillomyces, Trichoderma, Rhizopus, Fusarium and Syncephalastrum. The cellulolytic performances of mold on CMC media showed that Aspergillus flavus has the greatest cellulolytic ability.